A novel WSN key pre–distribution scheme based on group–deployment. (25th July 2014) - Zhou, Yucai; Wang, Tong; Wang, Yunfeng
Key pre–distribution scheme is one of the hotspots in wireless sensor network (WSN) security field. Most of the existing key pre–distribution schemes have the shortcomings such as low connectivity, poor resistance and scalability. This paper improves TD (k, n) model based on which a resolved TD (k, n) model is proposed. Then, furthermore, by combining the Blundo method and resolved TD (k, n) model, this paper proposes an improved sensor network key pre–distribution scheme IGDKPS (improved key pre–distribution scheme based on group deployment). Theoretical analysis and simulation results show that IGDKPS scheme has good performances in the security connectivity rates, resistance, flexibility and other aspects than the traditional methods.